FUNCTIONAL AND CULTURAL ASPECTS OF PHRASEOLOGICAL UNITS WITH A HUMAN COMPONENT IN ENGLISH - Toshtemirova Zulfiya Toshtemirovna; Aleksei Anatolievitch Kolesnikov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article analyses English phraseological units that contain a human component, meaning a lexical element naming a part of the body, a mental faculty, or a socially recognizable human feature such as face, heart, hand, tongue, blood, brain, backbone, and the like. Such units are not only stable combinations of words but also compact carriers of cultural knowledge, evaluation, and pragmatic force. The study argues that human component phraseology functions as a bridge between embodied experience and cultural interpretation.